Réveil des talents à l’université et place de l’enseignant-coach - Marie Machouart (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
enAt a time when amphitheatres are deserted by students and where ill-being is at the heart of the news, rethinking teaching methods is indispensable and leads to an inevitable evolution of the role of the teacher. When this role is combined with that of coach, the awakening of talents can then be favored. This raises the question of the adjustment of these postures in the accompanying processes of a young person, during delicate crossings towards fundamental transformations. The earliest possible detection of suffering among students is desirable and requires, however, a wide organization and involvement of a large number of people in universities. At the end of this journey in the wings of education, it is time to question about the emergence of strong educational alliances allowing these new impulses.